2020
DOI: 10.1142/s1793545820300074
|View full text |Cite
|
Sign up to set email alerts
|

Combating acoustic heterogeneity in photoacoustic computed tomography: A review

Abstract: Based on the energy conversion of light into sound, photoacoustic computed tomography (PACT) is an emerging biomedical imaging modality and has unique applications in a range of biomedical fields. In PACT, image formation relies on a process called acoustic inversion from received photoacoustic signals. While most PACT systems perform this inversion with a basic assumption that biological tissues are acoustically homogeneous, the community gradually realizes that the intrinsic acoustic heterogeneity of tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 69 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…The boundaries between tissues of highly contrasting acoustic properties (e.g., bone surfaces) reflect incident waveforms back towards the imaging probe, generating reflection artifacts [ 36 ] ( Figure 4 d), which may overlap with other image features of interest, or be mistaken as regions of actual optical absorption. Unknown variations in acoustic speed also challlenge reconstruction algorithms that naively assume constant SoS inside tissue, distorting the reconstructed images [ 39 ].…”
Section: Image Quality Limiting Factors In Clinical Optoacousticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundaries between tissues of highly contrasting acoustic properties (e.g., bone surfaces) reflect incident waveforms back towards the imaging probe, generating reflection artifacts [ 36 ] ( Figure 4 d), which may overlap with other image features of interest, or be mistaken as regions of actual optical absorption. Unknown variations in acoustic speed also challlenge reconstruction algorithms that naively assume constant SoS inside tissue, distorting the reconstructed images [ 39 ].…”
Section: Image Quality Limiting Factors In Clinical Optoacousticsmentioning
confidence: 99%
“…Many factors reduce or limit the quality of optoacoustic images, which, in turn, hinder the modality’s potential for clinical translation. These factors may emerge from the imaging hardware [ 25 , 26 , 27 , 28 , 29 , 30 ], the inexact or approximative image reconstruction algorithms [ 25 , 26 , 31 , 32 , 33 ], the attenuative properties and inhomogeneous nature of tissue (light-tissue interaction phenomena) [ 34 , 35 , 36 , 37 , 38 , 39 ], or particularities of the acquisition procedure [ 40 , 41 ], and manifest as image noise, artifacts, and poor overall image fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…The great diversity of possible hardware designs represents an important advantage of the OA technology [29]. On the other hand, significant variability of image formation approaches, independently developed for each particular configuration [30][31][32][33], may compromise reproducibility and reliability of the reported experimental results thus hindering the development of standardized methodologies enabling accurate quantification of bio-markers [34].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, considering that the SoS inside soft tissues varies from 1350 (fat) to 1700 m∕s (skin), 9,10 such an assumption can sometimes be too rough and can consequently cause splitting, blurring, and distortions of structural features, thus impeding many kinds of quantification tasks. 11,12 Studies have shown that, by integrating ultrasound tomography, the acoustic properties in the imaged field of view, including the SoS and acoustic attenuation, can be reconstructed at the expense of system complexity. [13][14][15] Another type of approach employs a model-based procedure to jointly reconstruct (JR) the acoustic properties and the photoacoustic IP by iteratively updating the numerical model to match the experimental data.…”
Section: Introductionmentioning
confidence: 99%